2017
DOI: 10.3390/ijms18122596
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol (E) Impairs Fetal Brain GSH Homeostasis by Inhibiting Excitatory Amino-Acid Carrier 1 (EAAC1)-Mediated Cysteine Transport

Abstract: Central among the fetotoxic responses to in utero ethanol (E) exposure is redox-shift related glutathione (GSH) loss and apoptosis. Previously, we reported that despite an E-generated Nrf2 upregulation, fetal neurons still succumb. In this study, we investigate if the compromised GSH results from an impaired inward transport of cysteine (Cys), a precursor of GSH in association with dysregulated excitatory amino acid carrier1 (EAAC1), a cysteine transporter. In utero binge model involves administration of isoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In a setting of reduced Cys availability as shown by us earlier [ 26 ] with increased accumulation of cystathionine levels (in the current study), we next determined whether this might be caused by an altered expression of CSE, a rate-limiting enzyme that metabolizes cystathionine to Cys. Immunoblotting experiments for CSE revealed that CSE protein was reduced with the treatment of E in fetal PCNs by 36%, 53% ( p < 0.05), and 64% ( p < 0.05) at 6, 12, and 24 h, respectively.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…In a setting of reduced Cys availability as shown by us earlier [ 26 ] with increased accumulation of cystathionine levels (in the current study), we next determined whether this might be caused by an altered expression of CSE, a rate-limiting enzyme that metabolizes cystathionine to Cys. Immunoblotting experiments for CSE revealed that CSE protein was reduced with the treatment of E in fetal PCNs by 36%, 53% ( p < 0.05), and 64% ( p < 0.05) at 6, 12, and 24 h, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…Consistent with this concept, we observed that alcohol caused a significant accumulation of cystathionine levels in the PCNs that was also replicated in the 2nd trimester equivalent in utero binge alcohol model and the 3rd trimester equivalent postnatal day (PN7) ethanol model as indicated by HPLC analysis. The resultant downstream impact of cystathionine accumulation on Cys and GSH levels were recently demonstrated by us [ 26 ]. Notably, previous reports in humans have shown that mutations of Cse gene causes an accumulation of cystathionine in liver, kidney, brain, and cerebrospinal fluid, leading to cystathionuria and decreased plasma cysteine concentration.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, experiments using ethanol in neurons, which impairs the expression of EAAC1 by 60-70%, revealed that the level of GSH and cysteine was reduced by up to 50% in primary cerebral cortical neurons. This effect was reversed by administration of NAC [22]. To increase the synthesis of GSH, EAAC1 is translocated to the plasma membrane and transports cysteine and glutamate into the neuron.…”
Section: Eaac1 and Glutathionementioning
confidence: 99%